Parents' perceptions of antenatal educational programs: A meta-synthesis. (October 2022) - Shorey, Shefaly; Loh, Doris Ngiuk Lan; Chan, Valerie; Chua, Crystal; Choolani, Mahesh A
Highlights: There is a lack of evidence to understand parents' perceptions of the contents and mode of delivery of antenatal educational programs. From our findings, parents requested antenatal educational programs to be inclusive and more specific to cater to their individual, cultural and community needs. Mindfulness strategies covered during antenatal programs were also well received. Additionally, deliberated efforts to foster social and professional networks are required. Abstract: Background: Contents and mode of delivery of antenatal educational programs differed considerably. Yet there is a lack of high-level evidence about the delivery of these programs. Objective: We aimed to understand the experiences and needs of parents who have attended antenatal educational programs. Design: Six databases were searched from each database. Included studies were appraised using the Critical Appraisal Skills Program tool. Qualitative data were meta-summarized and meta-synthesized. Findings: Seventeen studies were included, and three themes were developed: (1) Contradicting views on antenatal educational programs, (2) Feeling 'well prepared' after attending the antenatal educational programs, and (3) Parents' expectations and way forward for the antenatal educational programs. Discussion: Findings revealed that the description of contents of antenatal educational programs needed to be more specific. Mindfulness strategies were well-received by parents in the included studies. Educators should take into account inclusivity and increase educational resources related to individual, cultural and community needs. Learning needs can be assessed before and after classes. Parents with specific needs that were not addressed should be identified and referred to the relevant professionals for continued support. More deliberate actions were needed during the programs to foster social and professional networks for attendees to support them throughout antenatal and postnatal periods. Conclusion: We consolidated the experiences and needs of parents who have attended antenatal educational programs. Findings can help refine policies related to antenatal care to improve pregnancy, birth and parenthood experiences for both mothers and fathers.